2011
DOI: 10.1158/1055-9965.epi-10-1089
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Fat, Fiber, and Carbohydrate Intake in Relation to Risk of Endometrial Cancer

Abstract: Background Macronutrients such as fat and fiber have been hypothesized to play a role in the etiology of endometrial cancer. Methods To investigate these associations, the authors analyzed data from the Nurses’ Health Study (NHS). From 1980 to 2006, 669 invasive adenocarcinoma cases were identified over 1.3 million person-years of follow-up. Dietary intake was assessed in 1980 and updated every 2–4 years. Cox proportional hazard models were used to calculate relative risks (RRs), controlling for total energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 46 publications
1
28
1
Order By: Relevance
“…With the exception of PLCO, which observed significant reduced risk among women who consumed high GL diets (RR=0.63, 95% CI: 0.46, 0.84 for highest vs. lowest quartile) (25), most studies report non-significant elevations in endometrial cancer risk with GL or GI (26). Cohort studies observed elevated risks of 15% to 36% with high GL diets (pooled RR=1.22, 95% CI: 1.09, 1.37 for highest vs. lowest category), including the NHS (RR=1.29, 95% CI: 0.99, 1.67) (41), but not with GI (pooled RR=1.00, 95% CI: 0.87, 1.14) (26). In contrast, case-control studies observed significant increased endometrial cancer risk with GI (pooled OR=1.56, 95% CI: 1.21, 2.02), but the relationship with high GL diets was weaker (pooled OR=1.14, 95% CI: 0.91, 1.44) compared to cohort studies (26).…”
Section: Discussionmentioning
confidence: 99%
“…With the exception of PLCO, which observed significant reduced risk among women who consumed high GL diets (RR=0.63, 95% CI: 0.46, 0.84 for highest vs. lowest quartile) (25), most studies report non-significant elevations in endometrial cancer risk with GL or GI (26). Cohort studies observed elevated risks of 15% to 36% with high GL diets (pooled RR=1.22, 95% CI: 1.09, 1.37 for highest vs. lowest category), including the NHS (RR=1.29, 95% CI: 0.99, 1.67) (41), but not with GI (pooled RR=1.00, 95% CI: 0.87, 1.14) (26). In contrast, case-control studies observed significant increased endometrial cancer risk with GI (pooled OR=1.56, 95% CI: 1.21, 2.02), but the relationship with high GL diets was weaker (pooled OR=1.14, 95% CI: 0.91, 1.44) compared to cohort studies (26).…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Cui et al [280] (LOE IIb), no association was observed between the intake of n-3 fatty acids and risk of endometrial cancer.…”
Section: Quantity and Quality Of Dietary Fat And Fatty Acid Intakementioning
confidence: 96%
“…In the updated version of the WCRF report [261] (LOE IIa), MUFA were not covered for this carcinoma. The study by Cui et al [280] (LOE IIb) with data from the Nurses' Health Study , which has already been mentioned in a different context, showed no risk relation.…”
Section: Quantity and Quality Of Dietary Fat And Fatty Acid Intakementioning
confidence: 97%
See 1 more Smart Citation
“…A total of 16 published articles reporting risk factor of endometrial cancer satisfied the inclusion criteria and were included in our meta-analysis (Levi et al, 1993;Potischman et al, 1993;Shu et al, 1993;Tzonou et al, 1996;Goodman et al, 1997;Jain et al, 2000;McCann et al, 2000;Littman et al, 2001;Petridou et al, 2002;Folsom et al, 2003;Furberg et al, 2003;Xu et al, 2007;Bravi et al, 2009;Yeh et al, 2009;Biel et al, 2011b;Cui et al, 2011). The characteristics of the included studies were shown in Table 1.…”
Section: Eligible Studiesmentioning
confidence: 99%